2022
DOI: 10.3389/fpsyg.2022.804797
|View full text |Cite
|
Sign up to set email alerts
|

Is Distant Extension Always Upset? Neural Evidence of Empathy and Brand Association Affect Distant Extension Evaluation

Abstract: Distant brand extension as an essential strategy of obtaining benefits was highly focused on the normal marketing practice and academic research. In the current study, we aim to recognize that how individuals with different levels of empathy respond to distant extensions under corporate social responsibility (CSR) and corporate competence (CC) associations to explore the corresponding neural mechanisms using event-related potentials (ERPs). We divided subjects into two groups involving a high empathy (HE) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…As expected, the N2 and P3 components were induced by four conditions. Based on observation of the grand-averaged ERPs results and previous neuroscience studies, a time window of 200–270 ms was selected to analyze the mean N2 amplitude ( Shang et al, 2017 ; Jing et al, 2019 ; Ma et al, 2021 ) and a time window of 310–460 ms was used to analyze the mean P3 amplitude ( Fudali-Czyż et al, 2016 ; Shang et al, 2017 ; Song et al, 2022 ). For the N2 component, five electrodes distributed in the prefrontal-central region were selected for a 2 (product type: heaviness-positive product vs. heaviness-negative product) × 2 (presentation mode: saturated background vs. desaturated background) × 5 (electrode: F3, Fz, F4, FC1, and FC2) within-subjects repeated-measures ANOVA.…”
Section: Study 2: An Event-related Potential Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the N2 and P3 components were induced by four conditions. Based on observation of the grand-averaged ERPs results and previous neuroscience studies, a time window of 200–270 ms was selected to analyze the mean N2 amplitude ( Shang et al, 2017 ; Jing et al, 2019 ; Ma et al, 2021 ) and a time window of 310–460 ms was used to analyze the mean P3 amplitude ( Fudali-Czyż et al, 2016 ; Shang et al, 2017 ; Song et al, 2022 ). For the N2 component, five electrodes distributed in the prefrontal-central region were selected for a 2 (product type: heaviness-positive product vs. heaviness-negative product) × 2 (presentation mode: saturated background vs. desaturated background) × 5 (electrode: F3, Fz, F4, FC1, and FC2) within-subjects repeated-measures ANOVA.…”
Section: Study 2: An Event-related Potential Experimentsmentioning
confidence: 99%
“…Based on the S1-S2 paradigm, Han et al (2015) showed that a more negative N2 component is induced when S1 and S2 differ in color, shape, and direction. Furthermore, the N2 component is evoked by perception conflicts (Ma et al, 2007(Ma et al, , 2010(Ma et al, , 2021Shang et al, 2017;Song et al, 2020Song et al, , 2022. Wang et al (2016), for instance, asked participants to make purchase decisions based on product ratings and sales and found that the low product rating condition resulted in higher response conflicts, as reflected by the larger N2 amplitude.…”
Section: Introductionmentioning
confidence: 99%